Un procedimiento para estimar la humedad relativa, con fines agroecológicos, en medio tropical - García B, J.; Montoya Maquin, J.M. (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2025)
Based on data of 13 meteorological stations in Costa Rica, a relationship was established by fitting a linear regression between the relative humidity and montly precipitation. Furthermore, the relationship between slope (A) of each of these equations with the total annual precipitation (Pt) and the duration of the ecological dry season (N) was established yielding that following equation.